Process intensification of biodiesel synthesis via ultrasound-assisted in situ esterification of Jatropha oil seeds - Tan, Shiou Xuan; Ong, Hwai Chyuan; Lim, Steven; Pang, Yean Ling; Milano, Jassinnee (Wiley, 2019)
BACKGROUND: Non-edible oil such as Jatropha oil has high free fatty acids (FFAs) content. Therefore, acid esterification is a suitable route to reduce its FFA content to an acceptable limit (2 FFA%) before being subjected to further transesterification. In the present study, Jatropha seeds were utilized as the feedstock directly instead of Jatropha oil during ultrasound-assisted in situ esterification. The objective of this work is to evaluate the feasibility of in situ esterification of Jatropha oil seeds using sulphuric acid (H 2 SO 4 ) as catalyst with the aid of ultrasound. RESULTS: The reaction parameters (particle size, n-hexane to methanol volume ratio, H 2 SO 4 amount, reaction time and ultrasonic amplitude) were optimized and evaluated in term of extraction and esterification efficiencies as well as fatty acid methyl ester (FAME) yield. The highest extraction efficiency of 83.96%, esterification efficiency of 71.10% and FAME yield of 38.58% were achieved at particle size of 1–2 mm, n-hexane to methanol volume ratio of 3:1, 5 vol% of H 2 SO 4 and ultrasonic amplitude of 60% with reaction time of 150 min. CONCLUSION: Synthesis of biodiesel via ultrasound-assisted in situ esterification of Jatropha oil seeds was successful with considerable yield, which could provide improvement in terms of process intensification and more value added by-products. © 2018 Society of Chemical Industry. © 2018 Society of Chemical Industry